Mathematical Modelling and Release Behaviour of Drug - Dubey, Deeksha; Malviya, Rishabha; Kumar Sharma, Pramod (Drug Delivery Letters, 2014)
Dissolution of drug from solid dosage form is explained by kinetic models i.e. zero order, first order, higuchi model, Hixson-crowell cube root law, Korsmeyer-peppas and weibull model. These models are effective as design of new delivery device and the existing device is optimized by these models. In this study, these models are classified on two different bases. All these models are explained including their kinetic equations, plot which describes the relationship between drug release and time, and their applications. These models are best explained by examples including polymer and drug which show release behaviour following different models.
Keywords: release behaviour